2012
DOI: 10.1016/j.juro.2011.10.151
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Quality of Life and Psychosocial Adjustment in Patients With Renal Tumors Undergoing Open, Laparoscopic and Nephron Sparing Surgery

Abstract: Purpose We prospectively evaluated the general and cancer-specific quality of life (QOL) and psychosocial adjustment of patients with a renal mass who underwent radical versus partial nephrectomy performed by laparoscopic or open approaches. Materials and Methods 172 patients with renal tumors completed questionnaires before surgery and again at 3 weeks, 2, 3, 6, and 12 months post-surgery. We assessed general QOL (SF-36), cancer-specific-QOL (CARES-SF), intrusive thoughts and avoidance behaviors, and fear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 20 publications
0
50
0
1
Order By: Relevance
“…NSS versus RN, and the surgical access is just an incidental factor [9,22]. The present study shows that NSS, associated with flank surgery, predicts higher GFR.…”
Section: Discussionmentioning
confidence: 52%
“…NSS versus RN, and the surgical access is just an incidental factor [9,22]. The present study shows that NSS, associated with flank surgery, predicts higher GFR.…”
Section: Discussionmentioning
confidence: 52%
“…We recently showed, in one of the most comprehensive and largest QOL studies with patients undergoing different types of surgery for a renal mass (open radical, open partial, laparoscopic radical, or laparoscopic partial nephrectomy) who were assessed for 1 yr following surgery, that age had a great effect on how patients experience treatment of their cancer: Younger patients reported significantly less worry but more intrusive thoughts and behaviors [6]. In that study, we also found that all the physical benefits of a minimally invasive approach dissolved by 3 mo, while anxiety and worry over recurrence of cancer remained prominent 1 yr after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the spectrum of treatment options for small renal masses, WW represents the ultimate noninvasive and nephron-sparing approach. Recent prospective data have shown that age, renal function preservation, and tumor-related criteria (ie, size and pathologic stage) are independent predictors of quality of life (QOL) for patients undergoing surgical intervention for a renal mass [6]. In contrast, there appears to be little or no information on patient-derived outcomes for patients with a renal mass who are undergoing WW.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients treated with open PN or RN, there were no QoL differences 1 year after surgery, but renal functional preservation was noted to have a measurable patient‐reported QoL benefit . Comparatively, patients undergoing laparoscopic RN or PN have measurable short‐term patient‐reported QoL benefits, but the differences disappear after a few months ; however, patient fear of cancer and its recurrence, especially among older patients, remains an important factor at 1 year . Treatment options for localised RCC, therefore, have potential QoL implications, which merit consideration during treatment selection.…”
Section: Balancing the Peri‐operative Risks Of Radical Vs Nephron‐spamentioning
confidence: 99%